2022
DOI: 10.1155/2022/7459518
|View full text |Cite|
|
Sign up to set email alerts
|

Application Effect of Doctor-Nurse-Patient Integration Model Based on Heart Rate Management Strategies in Middle-Aged and Young Outpatients with Hypertension

Abstract: Objective. In this study, a doctor-nurse-patient integration management scheme based on heart rate (HR) management strategies was constructed to explore its application effect in the health management of young and middle-aged outpatients with hypertension. Methods. A total of 75 young and middle-aged patients with essential hypertension admitted to the Outpatient Department of Cardiology of Heji Hospital Affiliated to Changzhi Medical College, Shanxi Province, from October 2019 to July 2020 were selected and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…12 Furthermore, patients reasoned that picking a provider with more experience was more important during selection than provider type, thus influencing patients to pick nurse practitioners who fit these conditions. 12 As such, the current cosmetic landscape has begun to shift toward patients more commonly selecting nonphysician providers for completion of cosmetic procedures. Factors that may influence whether respondents choose physicians or non-physician providers included sex and procedure costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Furthermore, patients reasoned that picking a provider with more experience was more important during selection than provider type, thus influencing patients to pick nurse practitioners who fit these conditions. 12 As such, the current cosmetic landscape has begun to shift toward patients more commonly selecting nonphysician providers for completion of cosmetic procedures. Factors that may influence whether respondents choose physicians or non-physician providers included sex and procedure costs.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2016 study investigating patient perceptions about nurse practitioners in comparison to physicians, patients reported feeling that nurse practitioners were more holistic in their care. 12 Furthermore, patients reasoned that picking a provider with more experience was more important during selection than provider type, thus influencing patients to pick nurse practitioners who fit these conditions. 12 As such, the current cosmetic landscape has begun to shift toward patients more commonly selecting nonphysician providers for completion of cosmetic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%